2020
DOI: 10.3389/fpsyt.2019.00975
|View full text |Cite
|
Sign up to set email alerts
|

“Hidden” and Diverse Long-Term Impacts of Exposure to War and Violence

Abstract: Nowadays, the PTSD diagnosis is often a prerequisite for the survivor's access to specialized treatment services and for obtaining legal recognition or financial compensation when exposed to violence. However, some survivors do not meet all necessary criteria for the PTSD diagnosis, particularly not in the long term. Therefore, they run the risk of being misdiagnosed, inadequately helped or undertreated, and may remain legally unrecognized and unprotected. In this article the "hidden" long-term impacts of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…Trauma has been a major concern (Bryant et al, 2020). Some scholars have cautioned against overuse of the concept of trauma, based on scientific (Griffin, 2020), cultural (Drožđek et al, 2020), and methodological issues (Daiute, 2017). That said, the preponderance of researcher concerns about trauma and other psychological effects of the pandemic invokes the serious shock facing contemporary humanity.…”
Section: Adolescents In Crisis Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma has been a major concern (Bryant et al, 2020). Some scholars have cautioned against overuse of the concept of trauma, based on scientific (Griffin, 2020), cultural (Drožđek et al, 2020), and methodological issues (Daiute, 2017). That said, the preponderance of researcher concerns about trauma and other psychological effects of the pandemic invokes the serious shock facing contemporary humanity.…”
Section: Adolescents In Crisis Zonesmentioning
confidence: 99%
“…In times of crisis, narrating focuses intensely on what is important, how to interact with others, how to face threats, and, somehow, still to dream (Frankl, 1985). In addition to serving therapeutic functions (Drožđek et al, 2020), narrating in education and community practices integrates socioemotional and cognitive processes (Siller & Waibel, 2018).…”
Section: Dynamics Of Narrating In Crisis Zonesmentioning
confidence: 99%
“…Considering the multifactorial nature of the condition, the most straightforward approach for obtaining useful information with sufficient effect sizes regarding the prognosis of PTSD would be effective accumulation of risk factors by considering interaction among the factors. Several studies have demonstrated interactions among risk and protective factors for the prognosis of PTSD symptoms 5 9 . Satisfaction with social support has a significantly larger positive effect on the prognosis of PTSD symptoms in females than in males 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Loss of family members or lack of family support influences the prognosis of PTSD more in younger subjects than in older subjects 7 , 8 . Drožđek et al considers combinations of risk factors and shows the hidden long-term impacts of exposure to war and violence 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The fear psychosis in the region had to be understood in the light of the population in Northern Sri Lanka recovering from three decades of civil war, during which similar lockdowns and curfews were imposed, and the possible impact of psychological carryovers and traumatic flashbacks from this period. 6…”
mentioning
confidence: 99%